Empirical Study on the Currency Exchange Market. Determinants on the Exchange Rate of the U.S. Dollars and the Japanese Yen by the Regression Analysis. - Tokuichi (Tony) Komiya (Academicus International Scientific Journal, 2024)

(untitled)
It is widely known that in the exchange rate market there are three factors influential to determine the currency exchange rate between the related countries in theory; i.e., the interest rate, inflation, and expectation on the exchange rate. This paper aims to find how the exchange rate between U.S. dollar and Japanese Yen, both of which are widely recognized as major currencies in the international financial market, are affected by the four key variables selected here in this paper related to these three factors under the recent inflationary economic environment; i.e., interest rate yield of the two year treasury bond, inflation rate, and the two moving average of the exchange rate to be considered as rational expectation on the movement of the exchange rate. As result it is our discovery that the selected predicator variables have been influential to the daily volatility and monthly movement of the exchange rate of the Japanese Yen /US $ with evidence the two different models of the regression analysis are able to show the exchange rate are significantly correlated with these four key variables and strongly affected by them. Also, over 30-month study period, the interest rate parity or the purchasing power parity did not hold because of the strong US dollar and the continuous increase in interest rate yield during the rapid inflation in the US economy.